Umbilical Artery Thrombosis Masquerading as Single Umbilical Artery in a Stillbirth - Yin Ping Wong; Rahana Abd Rahman; Ay Eeng Tan; Geok Chin Tan (Diagnostics)
Background: Umbilical artery thrombosis (UAT) masquerading as a single umbilical artery (SUA) is a rare but critical diagnostic challenge in prenatal care. Case Presentation: We described a case of a 22-year-old primigravida with an uneventful obstetric history who presented with reduced fetal movements at 22 weeks of gestation. Ultrasound showed no gross fetal structural anomalies while umbilical artery Doppler flow imaging revealed an isolated SUA. The patient again presented with diminished fetal movement at 24 weeks gestation, and a diagnosis of intrauterine demise was confirmed ultrasonographically. She was then induced and delivered a macerated stillborn female fetus. Placental examination revealed three umbilical vessels with an occlusive thrombus seen within the umbilical artery consistent with UAT, a finding previously mistaken for SUA. Conclusions: This case underscores the diagnostic difficulties of UAT radiologically, especially when there was no prior documented evidence of two umbilical arteries. Identification of at-risk fetuses would allow for close monitoring or effective interventions to be implemented as early as possible to avert preventable fetal loss.